2021
DOI: 10.1093/rpd/ncab111
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dose Assessment and Optimisation of Pelvic Radiography With Computed Radiography Systems

Abstract: Digital radiography systems can reduce radiation dose, this capability was harnessed to explore dose and image quality (IQ) optimisation strategies. Entrance surface dose (ESD), effective dose (ED) and organ doses were determined by the indirect method for patients undergoing pelvic anteroposterior X-ray examinations with computed radiography systems. The IQ of patients’ radiographs was assessed in terms of signal-to-noise ratio (SNR). An anthropomorphic phantom was exposed with varying tube potential (kVp), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We evaluated three physical image quality parameters that are widely used in publications related to practice optimization in radiology [ [27] , [28] , [29] ]: Signal-to-noise ratio (SNR) that relates the useful information of the structure of interest (signal) to the variation in brightness level within a ROI (noise) [ 30 ]. We calculated SNR using Equation (1) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated three physical image quality parameters that are widely used in publications related to practice optimization in radiology [ [27] , [28] , [29] ]: Signal-to-noise ratio (SNR) that relates the useful information of the structure of interest (signal) to the variation in brightness level within a ROI (noise) [ 30 ]. We calculated SNR using Equation (1) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, information on paediatric imaging practices, equipment performance, and paediatric patient dose parameters are available, hence national DRLs for commonly used paediatric imaging procedures can be proposed. Furthermore, it also provides a clear path to establish guidelines for imaging paediatric patients and to recommend the use of appropriate and sound clinical justi cation before imaging paediatric and unborn child using high dose imaging modality such as CT imaging [2, 3,4]. Consequently, this will enable further analysis of the risk factors associated with paediatric CT examination, especially with the commonly used paediatric imaging procedures which account for approximately 90% of CT examinations in Ghana, that is head, abdomen, and chest examinations [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Abbeyquaye et al [3] studies emphasized the importance of optimizing radiographic examinations of the pelvic region, as they concluded that the patient may be exposed to an effective dose (ED) 20 times higher when compared to an examination of the chest. Although the average ED per examination in all plain radiographs is relatively low, for pelvic region examinations, it still represents higher values compared to other sites [4].…”
Section: Introductionmentioning
confidence: 99%